Influence of the environmental challenges on the resilience of purse seine fisherman in Kutaraja oceanic fishing port, Banda Aceh - Jasnur Syahputra; Sugeng Hari Wisudo; Eko Sri Wiyono; Mustaruddin Mustaruddin (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Purse seine fishermen in Kutaraja Oceanic Fishing Port, Banda Aceh, face various socio-economic and environmental challenges that affect the sustainability of their fishing activities. This study aims to identify and analyze the factors influencing the resilience of these fishermen in facing such challenges. A quantitative approach was employed through a survey method, and data were collected from 100 purse seine fishermen using structured questionnaires. The data were analyzed using descriptive and inferential statistics with multiple linear regression models. The findings show that income and social support significantly affect fishermens resilience, with p-values of 0.002 and 0.015 (p 0.05), respectively. Meanwhile, education and environmental conditions have less influence, indicated by p-values of 0.089 and 0.122 (p 0.05). The coefficient of determination (R) is 0.68, suggesting that 68% of the variance in fishermens resilience can be explained by these four variables. The practical implications of this research highlight the importance of empowering fishermen through enhanced access to education, skills training, and social infrastructure development to strengthen their resilience in dealing with environmental and economic changes in the fisheries sector. The study concludes that economic and social support systems are key drivers in improving fishermens adaptive capacity.Keywords:ResiliencePurse seineFishermenEnvironmentalBanda Aceh